Digital electronics logic and systems - Kershaw, John D. (Boston PWS-Kent Publishing Company, 1988)
Since the publication of the Second, the need for new or increased information in several subject areas has becom apparent. The most notable of these are: Boolean algebra with Karnaugh mapping New logic symbol are specified in International Logic Standards. Interface standards for the reception and transmission of digital date between electronic terminals.Standards such as RS232C, RS422A, and RS423A. High-speed CMOS logic circuits.
Keywords: Y Đa khoa